Optimal intrapleural therapy with alpha-hemolytic streptococci bio-product (Mannatide) in controlling malignant pleural effusion: a clustered systematic review and meta-analysis - Yan Zhang; Xiao-Tian Zheng; Jiao Xu; Da-Chun Cai; Feng Luo; Jun Huang; Yan-Yan Jin; Teng-Yang Fan; Ji-Hong Feng; Xue Xiao; Zheng Xiao (BMC Cancer)
Abstract Background Mannatide is an alpha-hemolytic streptococci bio-product. We conducted a comprehensive clustered systematic review and meta-analysis to reveal the clinical values of Mannatide for controlling malignant pleural effusion (MPE), identify the optimal therapeutic regimens, indications and usage, and assess their clinical effectiveness and safety. Methods We collected all eligible studies from both Chinese and English databases and clustered them into homogeneous comparisons or therapeutic regimens. We evaluated the risk of bias in eligible studies using RoB 2, pooled the data from each regimen using Review Manager 5.4, and summarized the quality of evidence. Results Seventy-eight studies met the eligibility criteria. Among six comparisons of perfusion with sclerosant alone, Mannatide showed only better complete response of MPE and lower pleurodesis failure and disease progression than interleukin-2. Among twelve combination therapeutic regimens, Mannatide and cisplatin might significantly improve the complete response (2.46, 2.07 to 2.91) and result in a low pleurodesis failure (0.28, 0.23 to 0.33) and disease progression (0.32, 0.21 to 0.48). For MPE with primary treatment, moderate to massive effusion, Karnofsky Performance Status ≥ 40 to 60 or anticipated survival time ≥ two to three months, perfusion with Mannatide at 20 to 50 mg/time, once per week and two to four times and cisplatin at 30 to 60 mg/time might achieve ideal clinical response. Most outcomes were moderate to low quality. Conclusion Mannatide may be a potential pleural sclerosant, which combination with cisplatin may represent a preferred therapeutic approach with a good clinical response and safety in controlling MPE. Trial registration PROSPERO CRD42022338798.